Energy harvesting of fully-flexible magnetoelectric composites using a piezoelectric P(VDF-TrFE) and magnetostrictive CoFe2O4 nanofiber. Issue 2 (21st November 2022) - Nam, Chaeyoung; Na, Yujin; Park, Sung Cheol; Kim, Hyunseung; Jeong, Chang Kyu; Hwang, Geon-Tae; Park, Kwi-Il
Abstract : A fully-flexible magnetoelectric (ME) composite with 2-2 type structure is developed by adopting CoFe2 O4 nanofiber-based magnetostrictive film and piezoelectric P(VDF-TrFE) and using simple electrospinning and spin-coating process. Abstract : In response to the increasing demand for wearable devices, the development of flexible energy harvesters as self-powering systems to replace batteries is accelerating. Flexible magnetoelectric (ME) composites, which can convert practical electrical energy from a magnetic field source, have attracted considerable attention for application in wearable magnetic devices. In this study, a 2-2 type structure based on a flexible magnetostrictive film with cobalt ferrite (CoFe2 O4, CFO) nanofibers was adopted to obtain appropriate flexibility and magnetoelectric properties. The flexible ME composite was completely fabricated by coating piezoelectric poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) onto a magnetostrictive film composed of CFO nanofibers and a polyimide matrix. Moreover, we conducted a multiphysics simulation and theoretically proved that a higher strain could be transferred to the piezoelectric layer at higher CFO concentrations, thus resulting in the generation of high magnetoelectric signals from the ME composite. The flexible, robust, and mechanically-stable ME composite reached an output voltage of 0.52 V and a current signal of 25 nA under an external AC magnetic field at 1 Hz. This study led to the development of a fully-flexible design of a bilayer ME composite prepared using a simple fabrication process providing a future avenue for wearable magnetoelectric energy harvesting.